Neotypification of Ophiorrhiza hunanica H. S. Lo (Rubiaceae), A species endemic to Hunan, China (Bangladesh Journal of Plant Taxonomy, 2014)
Not availableDOI: http://dx.doi.org/10.3329/bjpt.v21i2.21360Bangladesh J. Plant Taxon. 21(2): 193-195, 2014 (December)